Executive dynamic scheduling algorithm based on high-order heterogeneity - Hongyong JIA; Yunfei PAN; Wenhe LIU; Junjie ZENG; Jianhui ZHANG (Tongxin xuebao)
At present, most isomer scheduling models in DHR systems only considered second-order isomerism and lack dynamics.In order to solve these problems, a dynamic scheduling algorithm was proposed, which combined heterogeneity and dynamics by determining a scheduling scheme with maximum scheduling value.The value was obtained by combining high-order heterogeneity and historical information.The experimental results show that the proposed algorithm has better defense capabilities than other scheduling algorithms, and its strategy can achieve a balance of dynamics and security.